Semi-quantitative evaluation of protein residues in foods using the FLASH™ rapid cleaning validation method - Olds, David A.; Fung, Daniel Y. C.; Shanklin, Carol W. (My University, 2008)
Cross-containination of food contact surfaces in retail foodservice establishments may result in outbreaks of foodborne illness. Traditional microbiological sampling collection methods that use swab tests or agar surface tests to monitor cross-contamination can be time- and cost-prohibilive to restaurant operators. The purpose of this study was to develop tin identification. protocol for residual proteins on foodservice contact surfaces using rapid chemical detection methods. The FLASH Rapid Cleaning Validation device (BioControl S),stems, Bellevue, WA, was used to detect residual protein traces (exposed for 0, 2, 4, 6 and 8 h) of six different food samples (ground beef ground turkey, ground pork, catfish, shredded cheddar cheese and shredded vegetables) on plastic cutting boards. Catalase testing was performed concurrently with FLASH validation to add further estimation of potential biological activities. Results showed that meat, cheese and vegetable samples were positive for the FLASH test and could provide semiquantification using a red-green-blue color chart. In addition, catalase testing provided more selective identification of food samples. This study demonstrates the time savings and cost-effectiveness of using rapid methods of monitoring food safety standards in a foodservice operation.
Keywords: Protein; Rapid; Food service; Cross-contamination; Food; Safety